Occurrence of Covid-19 in different communities in Kolkata - Mukhopadhyay, Jyotishman; Chatterjee, Anant; Mallik, Debayan; Chatterjee, Chitra (Asian Journal of Medical Sciences, 2021)
Background: Scourge of ongoing COVID-19 pandemic is a matter of public health concern. New-norm preventive life-style like use of mask, repeated hand washing, social distancing and hygienic way of coughing-sneezing often compromise easy life and personal comfort. Earlier studies established certain epidemiological aspects of COVID-19 mostly in highend societies, but not many conducted on occurrence of COVID-19 in low-middle-income communities to ascertain the trend. Aims and Objective: Considering a possible upsurge of COVID-19 in Kolkata, it was decided to study the occurrence of COVID-19 in the background of preventive awareness and its application among residents in three different communities in Kolkata. Materials and Methods: Study was conducted in three different communities located in south Kolkata during Apr 20 to Mar 21. Community 1 and 2 were semi-urban clusters and Community 3, a high profile society; having 266, 282 & 360 adults respectively. Consent was taken from authority as well as individual subjects. Questionnaire was made incorporating personal attributes, knowledge of personal protective measures (PPM) & its application; lastly details of COVID-19 patients. Questionnaire was sent to willing members through e-mode; those declined were contacted individually following new-norm. Data collected was coded for confidentiality, tabulated and analysed. Confirmed COVID-19 (RT-PCR+ve) declared by Govt/private hospitals during Apr 20 to Mar 21 were included. Result: Communities studied had analogous demographic traits. Two communities belonged to low-SES group, while other enjoyed high-end-status. Almost 90% of slum/colony dwellers knew all facets of COVID-19 prevention compared to cent-percent of upper class people. 52% in one and around 93-100% in other two groups followed recommended PPM. Occurrence rates of COVID-19 infection were 11.3, 10.6 & 11.1 per 1000 adult of respective communities during study period. Affected were mostly male (90%) of 30-44 year age with 60% from low SES & 40% from the privileged. Many indisposed used masks (70%), washed hands (100%) and followed social distancing (90%). Study unfurled the explicit distinctiveness of COVID-19 infection irrespective of social stand aside idealistic reflective of preventive awareness/application. PPM though renders protection but its circumventing role needs consistent application in back-lore of certain contextual considerations. Conclusion: Further research is recommended to enrich this endeavour to explore facts that may play vital role in COVID-19 prevention in future.